2022
DOI: 10.1101/2022.01.21.477192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglia integration into human midbrain organoids leads to increased neuronal maturation and functionality

Abstract: The human brain is a complex, three-dimensional structure. To better recapitulate brain complexity, recent efforts have focused on the development of human specific midbrain organoids. Human iPSC-derived midbrain organoids consist of differentiated and functional neurons, which contain active synapses, as well as astrocytes and oligodendrocytes. However, the absence of microglia, with their ability to remodel neuronal networks and phagocytose apoptotic cells and debris, represents a major disadvantage for the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 76 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Whole-cell patch-clamp and multi-electrode array recordings showed that a lower threshold for action potential generation and a shorter interspike interval were observed in microglia-integrated midbrain organoids, suggesting that microglia integration promoted neural maturation. The presence of microglia in midbrain organoids also increased cytokine release (including IL6, IL10, IL1β, and TNFα), and affected expression of genes related to immune response, inflammation, phagocytosis, and synaptic remodeling and maturation [85].…”
Section: D Cultured Mc-hbosmentioning
confidence: 97%
See 2 more Smart Citations
“…Whole-cell patch-clamp and multi-electrode array recordings showed that a lower threshold for action potential generation and a shorter interspike interval were observed in microglia-integrated midbrain organoids, suggesting that microglia integration promoted neural maturation. The presence of microglia in midbrain organoids also increased cytokine release (including IL6, IL10, IL1β, and TNFα), and affected expression of genes related to immune response, inflammation, phagocytosis, and synaptic remodeling and maturation [85].…”
Section: D Cultured Mc-hbosmentioning
confidence: 97%
“…Excitatory post-synaptic currents (EPSCs) were present only in neurons from microglia-containing organoids after day 107 [84]. A recent study [85] that co-cultured human midbrain organoids with hiPSCs-derived macrophage progenitors also reported that microglia integration led to increased neural maturation and functionality. Whole-cell patch-clamp and multi-electrode array recordings showed that a lower threshold for action potential generation and a shorter interspike interval were observed in microglia-integrated midbrain organoids, suggesting that microglia integration promoted neural maturation.…”
Section: D Cultured Mc-hbosmentioning
confidence: 99%
See 1 more Smart Citation